Molecular characterization of virulence factors in Aeromonas hydrophila obtained from fish - Oliveira,Samira T.L. (2012)
Multiple factors can be involved in the virulence processes of Aeromonas hydrophila. The objective of the present paper was to verify the presence of aerolysin, hidrolipase, elastase and lipase virulence genes through the polymerase chain reaction (PCR) in A. hydrophila isolates obtained from fish of the São Francisco River Valley, and to evaluate virulence according to the presence of these genes in Nile tilapia fingerlings. One hundred and fourteen isolates from the bacteria were used. DNA was heat extracted and PCR undertaken using specific primers described in the literature. For in vivo tests Nile tilapia fingerlings were used. From the PCR tests, negative isolates for all genes tested were selected, positive isolates for two genes (aerolysin and elastase) and positive for the four genes tested. These were inoculated at a concentration of 10(8) UFC/ml into the tilapias, considered as treatments; another group of animals was used as control (with inoculation of saline solution). In all, 12 distinct standards regarding the presence of virulence factors in isolates from A. hydrophila, were observed. Of the 114 isolates analyzed, 100 (87.72%) presented at least one of the virulence factors under study. The virulence factors were widely distributed among the A. hydrophila isolates. Aerolysin was the most frequent virulence factor present in the isolates analyzed. A. hydrophila led to the mortality of the Nile tilapia fingerlings, regardless of the absence or quantity of virulence genes tested.